Efeitos dos antioxidantes associados à crioterapia na resposta inflamatória após exercícios resistidos em voluntários sedentários - Brito, Edineia de (2018)
Resistance exercises (RE) or bodybuilding promote many adaptations in the body, where the training and the type of program influence the physiological adaptations, allowing medium and long term favorable effects on the quality of life. However, this practice generally induces an acute inflammatory response, which can arise as a result of tissue damage resulting from mechanical stress (which causes lesions in contractile and connective tissues) and/or metabolic stress (hormonal activation and its consequences) causing lesions of the cellular components. This is due in part to oxidative stress, which induces the inflammatory response that accompanies leukocytosis. These events are responsible for the discomfort and the decrease of the function after the exercises, which favor the abandonment of the physical activity. However, the use of exogenous antioxidant agents and cryotherapy may reduce oxidative stress and consequently musculoskeletal tissue damage from high intensity ER. However, the association between antioxidants (vitamins C and E, pre-exercise) and cryotherapy (immersion in water at 15ºC, post-exercise) have not yet been evaluated in high intensity RE. The objective of this study is to compare the effects of antioxidants associated with cryotherapy on the parameters of oxidative stress, inflammatory markers and leukocytosis in response to an ER session in sedentary volunteers. The present study is characterized as a single-blind, randomized, single arm Randomized Clinical Trial performed with fourteen healthy sedentary volunteers. The study comprised the evaluation of muscle strength in four ER sessions with seven-day intervals. Muscle strength was assessed by 10 maximal repetitions (10RM). The interventions comprised: passive recovery, recovery with vitamins C (1g) and E (800UI) 40 min pre-exercise, recovery with cryotherapy (immersion at 15ºC for 10 min) immediately after exercise and recovery with the association of vitamins and cryotherapy. Hemoglobin, fibrinogen, C-reactive protein (CRP), creatine kinase (CK), lipoperoxidation (LPO), antioxidant capacity against peroxyl radical (ACAP) were evaluated at baseline, 0min, 30min and 120min. Delayed onset muscle soreness (DOMS) was assessed 24 h after ER sessions. CRP (120min) and CK (0min, 30min, 120min) increased only in the control session. Recovery with the combination of interventions attenuated the increase of young neutrophils, inflammatory markers, oxidative stress, and reduced DOMS after a RE session in sedentary volunteers, being able to help in the recovery of athletes in competition, as well as, beginners in this sport modality reducing the practice abandonment.